2011
DOI: 10.15376/biores.6.3.2719-2731
|View full text |Cite
|
Sign up to set email alerts
|

Media selection for mycelia growth, antifungal activity against wood-degrading fungi, and GC-MS study by Pycnoporus sanguineus

Abstract: Wood-decaying fungi present a serious threat to items made from rubberwood (Hevea brasiliensis). Though conventional chemical control has been a successful method for preserving wood against stain and decay fungi growth, the effects of these chemicals are of concern because they create problems for the environment and public health. Pycnoporus sanguineus (P. sanguineus), is a white-rot fungus that invades wood during its growth, storage, or use, causing decay or other property changes. It was considered in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In this regard, it was found that flavonoids secreted as plant exudates act as chemical attractants to Rhizobia [76]. Moreover, 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl, which is determined as a major flavonoid compound in the present study, has been reported as an antifungal agent [77]. Indeed, root exudates act as chemical messengers to regulate the microbial chemotaxis and interactions via a diverse array of molecular networks [78].…”
Section: Discussionsupporting
confidence: 49%
“…In this regard, it was found that flavonoids secreted as plant exudates act as chemical attractants to Rhizobia [76]. Moreover, 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl, which is determined as a major flavonoid compound in the present study, has been reported as an antifungal agent [77]. Indeed, root exudates act as chemical messengers to regulate the microbial chemotaxis and interactions via a diverse array of molecular networks [78].…”
Section: Discussionsupporting
confidence: 49%
“…4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl-(DDMP) is a fraction of flavonoid that was detected in almost all samples except for H3 and H8. It had been reported as antifungal (Teoh et al, 2011).…”
mentioning
confidence: 99%
“…(2011) conducted a study to investigate the optimum medium composition for mycelial growth and antifungal activity of P. sanguineus. In this work, they found out that 10 g/l ME, YE, dextrose and maltose supported the highest fungal growth [27]. In the presence of readily available reducing sugar, fungi produce high levels of Lac enzyme [40].…”
Section: Enzyme Activitiesmentioning
confidence: 77%
“…Table 1 shows the concentration ranges of the medium components used in this study. The components and concentrations were selected as an interpretation of the authors' of the present study based on previous optimization studies on P. sanguineus [27] , Pleurotus ostreatus [28], and Phlebia brevispora [29]. The experiments performed were early exploratory investigations to understand the effect of nitrogen sources on the enzyme production.…”
Section: Fungal Growth and Enzyme Productionmentioning
confidence: 99%